1D Coordination Polymer Nanofibers for Low‐Temperature Photothermal Therapy. Issue 40 (21st August 2017) - Yang, Yu; Zhu, Wenjun; Dong, Ziliang; Chao, Yu; Xu, Lai; Chen, Meiwan; Liu, Zhuang
Abstract: Near‐infrared (NIR)‐light‐triggered photothermal therapy (PTT) usually requires hyperthermia to >50 °C for effective tumor ablation, which can potentially induce inflammatory disease and heating damage of normal organs nearby, while tumor lesions without sufficient heating (e.g., the internal part) may survive after treatment. Achieving effective tumor killing under relatively low temperatures is thus critical toward successful clinical use of PTT. Herein, we design a simple strategy to fabricate poly(ethylene glycol) (PEG)‐modified one‐dimensional nanoscale coordination polymers (1D‐NCPs) with intrinsic biodegradability, large surface area, pH‐responsive behaviors, and versatile theranostic functions. With NCPs consisting of Mn2+/indocyanine green (ICG) as the example, Mn‐ICG@pHis‐PEG display efficient pH‐responsive tumor retention after systemic administration and then load Gambogic acid (GA), a natural inhibitor of heat‐shock protein 90 (Hsp90) that plays an essential role for cells to resist heating‐induced damage. Such Mn‐ICG@pHis‐PEG/GA under a mild NIR‐triggered heating is able to induce effective apoptosis of tumor cells, realizing low‐temperature PTT ( 43 °C) with excellent tumor destruction efficacy. This work not only develops a facile approach to fabricate PEGylated 1D‐NCPs with tumor‐specific pH responsiveness and theranostic functionalities, but also presents a unique low‐temperature PTT strategy to kill cancer in a highly effective and minimally invasive manner. Abstract : A one‐dimensional (1D) PEGylated nanoscale coordination polymer (NCP) is fabricated via a one‐step method. After loading gambogic acid (GA), such Mn‐ICG@pHis‐PEG/GA displays efficient pH‐responsive tumor retention after systemic administration. Owing to the GA‐induced down‐regulation of Hsp90 to overcome the thermal‐resistance of tumor cells, highly effective in vivo destruction of tumors is relized with Mn‐ICG@pHis‐PEG/GA under low‐temperature photothermal therapy at 43 °C.